THE POLITICS OF KNOWLEDGE PRODUCTION IN POST-GENOCIDE RWANDA (The Strategic Review for Southern Africa, 2020)
Looking beyond obvious development achievements under Kagame's rule, this article attempts to reveal the political motives behind the government's large-scale campaign to rewrite the country's history and to reshape society. In order to do so, the political practices of the current regime are analysed from a critical approach based on the writings of Foucault and Agamben. The article examines how the survival of the current regime is securitised and what role censorship along with propaganda play in strengthening the current government. Moreover, it exposes what political motives are at the bottom of collective mourning ceremonies and how one part of the population is victimised while the other part is criminalised. In Rwanda, 'peace' equals 'security' which is imposed by an all-powerful state through tight control over all aspects of life — including the productionof knowledge and the definition of 'truth'. In such an environment, the renewed politicisation of ethnicity or any other cleavage in society might easily erupt in another wave of violence.The intellectual's role is first to present alternative narratives and other perspectives on history than those provided by the combatants on behalf of official memory" (Said 2002: 37).